Recent Advances in Organic Light-Emitting Diodes Based on Pure Organic Room Temperature Phosphorescence Materials - Zhan, Ge; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui (Frontiers in Chemistry, 2019)
Pure organic room temperature phosphorescence (RTP) materials have attracted extensive attention in recent years due to their unique characteristics, such as flexible design method, low toxicity, low cost, and easier scale production. The involvement of triplet state and direct radiative transition from the triplet state make RTP materials great potential for a new generation emitters in organic light-emitting diodes (OLEDs). Based on the mechanism of phosphorescence, various methods have been developed to achieve RTP emissions in crystal state. However, the observation of RTP in thin film state is much more difficult because of the lower degree of rigidity and suppression of non-radiative transition. In this mini-review, molecular design strategies developed to achieve RTP emissions and their application in OLEDs are summarized and discussed. The conclusion and outlook are presented to point out the great potential and challenges for further study on pure organic RTP materials based OLEDs.